Методи та алгоритми балансування штучного інтелекту для ігор жанру FPS - Кісельгова, М. Є. (ХНУРЕ, 2024)
This research focuses on optimizing artificial intelligence (AI) for enemy behavior in FPS (First-Person Shooter) games to enhance the gaming experience. AI plays a pivotal role in creating realistic and engaging enemy characters, directly influencing game difficulty and player immersion. This study conducts a comparative analysis of existing AI balancing algorithms and methods used for enemy behavior, proposing an optimized approach based on the analysis of player preferences. By selecting the most relevant balancing parameters, this research aims to develop a more adaptive and challenging AI, contributing to a deeper and more captivating gameplay.
Keywords: AI; First-Person Shooter; штучний інтелект